Undergraduates’ understanding of what it means to lie - Maki, Alina J. K.; Alexander, Patricia (Frontiers in Education, 2025)
This study investigated how undergraduate students define a lie and apply their definition when given more context in the form of scenarios. Sixty-five undergraduate students responded to questionnaires asking them to define a lie and then decide whether a lie was spoken along with a justification for their decision. All students determined that a lie contains a falsehood. However, there was disagreement about whether a speaker needed to intentionally tell a falsehood for a statement to be a lie. In addition, there was no single scenario that prompted unanimous agreement among the students as to what constituted a lie. Inconsistencies were documented between students’ personal definition of lies and the criteria they used to judge lies in the scenarios. Overall, this study contributed to the extant literature by investigating undergraduates’ perceptions of lies, comparing those definitions to their contextualized judgments, and gathering detailed justifications explaining their reasoning. The study also provides avenues for future research.